Real‐world experience in treating pediatric relapsed/refractory or therapy‐related myeloid malignancies with decitabine, vorinostat, and FLAG therapy based on a phase 1 study run by the TACL consortium. Issue 10 (21st June 2022) - Schafer, Eric S.; Chao, Karen; Stevens, Alexandra M.; Jo, Eunji; Hilsenbeck, Susan G.; Gossai, Nathan P.; Doan, Andrew; Colace, Susan I.; Guinipero, Terri; Otterson, Daniel; Kaplan, Joel A.; Hinson, Ashley; et al.
Abstract: Current therapies for relapsed/refractory (R/R) pediatric myeloid neoplasms are inadequately effective. Real‐world data (RWD) can improve care by augmenting traditional studies and include individuals not eligible for clinical trials. The Therapeutic Advances in Childhood Leukemia and Lymphoma (TACL) consortium recently completed T2016‐003, a phase 1 study of decitabine, vorinostat, fludarabine, cytarabine, and granulocyte colony‐stimulating factor (G‐CSF) in R/R acute myeloid leukemia (AML), which added epigenetic drugs to a cytotoxic backbone. We report results of RWD from six centers that treated 28 pediatric patients (26 with AML, two with other myeloid neoplasms) identically to the TACL study but who were not enrolled. This allowed unique analyses and the ability to compare data with the 35 TACL study patients. The overall response rate (ORR) (complete response [CR] plus CR with incomplete count recovery) among 26 RWD evaluable patients was 65%. The ORR of 13 patients with relapsed AML with epigenetic alterations was 69% (T2016‐003 + RWD: 68%, n  = 25), of eight patients with refractory AML was 38% (T2016‐003 + RWD: 41%, n  = 17) and of five patients with therapy‐related AML (t‐AML) was 80% (T2016‐003 + RWD: 75%, n  = 8). The mean number of Grade 3/4 toxicities experienced by the T2016‐003‐eligible RWD population ( n  = 22) (one per patient‐cycle) was not meaningfully different than those ( n  = 6) who would have been TACL study‐ineligible secondary to comorbidities (two per patient‐cycle). Overall, this therapy was well tolerated and effective in pediatric patients with R/R myeloid neoplasms, particularly those with epigenetic alterations, t‐AML, and refractory disease.